Aderência aço-concreto: simulação numéricadosensaios de arranchamento pull-out e APULOT usando o programa ATENA - Tavares, Alysson José [UNESP] (2014)
The bond between steel and concrete is essential for the existence of reinforced concrete structures, as both materials act together to absorb structural strain. The bond phenomenon is considered to be complex regarding many factors that affect it. Several types of bond tests have been proposed over years. One is the modified proposed of pull-out test, which was elaborated by Lorrain and Barbosa [1] called APULOT test (Appropriete pull-out-test). Based on experimental results obtained by Vale Silva[2] either by conventional pull-out tests, or by modified pull-out test, APULOT, seeks to know the numeric behavior of bond steel-concrete through a numerical simulation using a calculation code ATENA which is based on the Finite Element Method (FEM). The numerical simulation provided better evaluate the stress distribution and cracking that occurs during the test, thereby becoming a valuable tool to support the experimental project that aims to validation, validation partially or not recommend the modified bond test steel-concrete - APULOT test - as quality control test of structural concrete. The numerical results showed good representation compared to experimental results.